Beyond states and non-state actors: the role of state-empowered entities in the making and shaping of international law - Sivakumaran, Sandesh (Columbia Law School, 2017)
Traditionally, the actors in the international legal sys-tem are divided into States and non-state actors; and States are considered to be the ones that make and shape international law. By contrast, this Article argues that there is a third category of actors, namely state-empowered entities, which have been empowered by States to make and shape international law. These entities are not States, but due to their empowerment by States, they are also not non-state actors. Accordingly, they constitute a category in and of themselves. Entities of this type include the International Law Commission, the United Nations Human Rights Committee, and the International Committee of the Red Cross. The making and shaping of international law includes the interpretation, application, and development of the law. States continue to play a role in the making and shaping of international law, for example, through establishing the mandate of the state-empowered entity, feeding their views into the work product of the entity, and assessing the final out-put of the entity. However, in practice, States rarely engage with the work-product of state-empowered entities and, in failing so to engage, have ceded some of their influence in lawmaking. This silence on the part of States has been treated as acquiescence to the work-product of state-empowered entities and the gap left by the lack of engagement has been filled by other members of the community of international lawyers. The day-to-day making and shaping of international law is thus being done less by States and more by state-empowered entities.